Ekosistem Transformatif Pendidikan Informal: Konstruksi Karakter Kasih Sesama pada Santri SPMAA Bali: Transformative Ecosystem of Informal Education: Building a Character of Compassion for Others among Students of SPMAA Bali - Savio Bhirawa Anoraga Muchtar; Supriyono Supriyono; Zulkarnain Zulkarnain (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The formation of a compassionate character in the younger generation faces serious challenges amidst the flow of individualistic modernity. Islamic boarding schools as informal educational institutions have transformative potential that has not been systematically analyzed, especially in the context of cultural and religious pluralism. This study aims to uncover and analyze the construction of the informal educational ecosystem of the SPMAA Denpasar Islamic Boarding School, Bali, in forming a compassionate character in students through community service activities. The study used a qualitative approach with a single case study design. Data were collected through semi-structured in-depth interviews, participant observation, focus group discussions, and documentation of 11 purposively selected informants, during the period August–November 2025. Data analysis used the interactive model of Miles and Huberman, following the stages of data reduction, data display, and concluding, with triangulation of sources and methods. The study identified a transformative ecosystem comprising nine integrated elements. The main findings show that the 24-hour total immersion architecture with an allocation of 65% informal character education (tadib) to 35% academic (talim), combined with community service as an authentic character laboratory in the context of Balinese plurality, is a dominant factor in the internalization of the value of compassion for others holistically and sustainably. The character transformation that occurs is ontological, marked by a shift in students' lives from a materialistic to an altruistic orientation. This research contributes to the development of the theory of the informal education ecosystem in Islamic boarding schools. It provides a practical model for cross-cultural character formation relevant to Non-Formal Education in pluralistic Indonesia.